Metadiscourse Markers in Scientific Journal Articles - Veronica Esti Nugrahani; Barli Bram (Langkawi: Journal of The Association for Arabic and English, 2020)
This paper aimed to investigate the use of metadiscourse markers in scientific journal articles. Data of this qualitative research consisted of metadiscourse markers collected from eight journal articles of a special edition published by LLT Journal: A Journal on Language and Language Teaching.  The collected metadiscourse markers used in the journal articles were analyzed using discourse analysis based on ten metadiscourse marker categories. Results showed that the analysed journal articles contained 708 metadiscourse markers, with more interactive metadiscourse markers, reaching 529 occurrences, than interactional metadiscourse markers, occurring 179 times. Transitions, such as “but” and “thus”, with 249 occurrences, were the most frequently-used metadiscourse marker and boosters, such as “in fact” and “definitely”, with 24 occurrences, were the least productive marker.  Thus, readers can gain a better understanding of the use of metadiscourse markers when using English. It is expected that English language learners and instructors can benefit from the results of this study, particularly concerning the use of metadiscourse markers in academic writing.